Lietuvos TSR žemės ūkio mokslinės-techninės informacijos sistema - Zinkevičienė, Julija (Knygotyra, 1983)
One of the main tasks noted in the XXVIth Congress of the Soviet Union Comunist Party is the realization of its agrarian policy. Scientific and technical information system was created in order to achieve the aims which were raised for agriculture by the Comunist Party and our government. The Agricultural Scientific and Technical Information System started in 1969 in Lithuania. It consists of several levels: the Central Scientific and Technical Information Bureau, 5 sectors of scientific information and propaganda in the agricultural scientific research institutes the information departments in the regional agricultural offices, the information groups in the soviet and collective-farms and the libraries of the agricultural high and profesional schools. The main aim of the Republican Agricultural Scientific and Technical Information System is to form the unity of the scientific achievements and agricultural industry.